Pengaruh Pemanfaatan Teknologi Aplikasi Penjualan Online terhadap Pertumbuhan Ekonomi UMKM Produk Lokal di Indonesia - Senna Hendrian; Ambar Tri Hapsari (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This study aims to analyze the effect of utilizing online sales application technology on the economic growth of local product-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The rapid advancement of digital technology has encouraged MSMEs to integrate online sales applications into their business processes to enhance competitiveness and business sustainability. This research employs a quantitative explanatory approach using survey data collected from MSME actors who actively utilize online sales application technology. The independent variable in this study is the utilization of online sales application technology, while the dependent variable is MSME economic growth, measured through sales growth, income growth, and market expansion. Data were analyzed using multiple linear regression, including t-test, F-test, and coefficient of determination (R²). The results indicate that the utilization of online sales application technology has a positive and significant effect on MSME economic growth. These findings emphasize the strategic role of digital technology adoption in strengthening MSME performance and supporting inclusive economic growth in Indonesia. The study provides important implications for policymakers and stakeholders in promoting digital transformation among MSMEs.